The Relationship Between Fiber Intake and Omega 3 and 6 Fatty Acid intake and Metabolic Syndrome in 4 Countries Spanning the Epidemiologic Transition. (29th May 2020) - Mehta, Supal; Dugas, Lara; Luke, Amy
Abstract: Objectives: Dietary modifications can be an effective therapeutic approach to prevent and manage metabolic syndrome. The aim of this study is to explore the association between fiber intake with metabolic syndrome and between omega 3 and 6 fatty acids with metabolic syndrome in four countries spanning the epidemiological transition. The study participants eat very different diets across the countries. Methods: Data were obtained from a cohort of 2000 adults, aged 25–45, enrolled in the Modeling the Epidemiologic Transition Study from US, Ghana, Jamaica and Seychelles. Dietary intake was measured using two 24hr recalls and analyzed using Nutrient Data System for Research. Participants were categorized as having metabolic syndrome if they had at least three of the following condition: high triglyceride levels (>150 mg/dL), reduced high-density lipoproteins (<40 mg/dL), elevated blood pressure (>130/85 mmHg), increased fasting blood glucose (>100 mg/dL) and a waist circumference (>89 cm for women and >103 cm for men). The association between fiber and metabolic syndrome was analyzed using quartiles of total, soluble, and insoluble fiber intake. The association between metabolic syndrome and the combined intake of omega 3 and 6 fatty acids was analyzed using quartiles of the omega 3 index, the sum of eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), and quartiles of the ratio of omega 6:3 fatty acids. Data were analyzed using logistic regressions adjusted for age, sex, calorie intake, alcohol intake and smoking status. Results: Participants with metabolic syndrome were 1.7 times (95% CI: 1.2, 2.3) as likely to be in the lowest compared to the highest quartile of total fiber intake and 1.5 times (1.1, 2.0) as likely to in the lowest quartile of insoluble fiber intake. Participants with metabolic syndrome were 1.9 times (1.3, 2.7) as likely to be in the lowest quartile of the of EPA + DHA intake. Risk of metabolic syndrome was not significantly associated with omega 6:3 ratio. Conclusions: These findings expand on prior research supporting a beneficial role for dietary fiber and omega 3 fatty acids in reducing the risk of metabolic syndrome in understudied populations consuming a wide range of diets. In aggregate, these results support an important role of diet in metabolic syndrome risk regardless of population. Funding Sources: National Institute of Health. Stritch School of Medicine.